EVALUASI PENGGUNAAN ANGGARAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DESA TAHUN 2017 - CYNTIA PRAMESTI; YUSUARSONO YUSUARSONO; BANDO AMIN C.KADER (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
This study aims to evaluate the use of village fund budget in supporting village development in 2017 in Pulogeto Baru village, Merigi Sub-District, Kepahiang Regency. The theory used was the theory of program evaluation by Wirawan. The method used was descriptive method with a qualitative approach. The number of informantsin this study were 8 people consisting of: 4 key informants and 4 key informants. Data collection was done through interviews, observation, documentation and literature study. Data analysis techniques used were data reuction, data presentation and conclusion drawing.based on the results and discussin it is known that the evaluation of the use of village funds in supporting village development in 2017 is more about infrastructure development. There are several processes in accordance with Minister of Home Affairs regulation Number 113 of 2014. And has produced the Pulogeto Baru Village Regulation Number 2 of 2017 concerning the Village Budget 2017. APBDes still has obstacles during the planning, reporting, and accountability processes that have not fully involved the community. And the people of Pulogeto Baru Village have benefited from the development that has been done such as the construction of concrete rebate roads, environmental sanitation and BUMDesa management called Dio Ba Gite which is engaged in barber business, LPG gas sales and fertilizer sales. Thus, it can be concluded that Pulogeto Baru village government has used the village budget well.